Web-Based System Information Certificate Services at Klamono District Offices - Arief, Muhammad Nur; Setyawan, Muhammad Rizki; Soekarta, Rendra; Simori, Pascalina Magrice (Universitas Muhammadiyah Yogyakarta, 2023)
Klamono District Office still relies on manual procedures for delivering certificates to residents, involving steps such as direct submission of certificate requests at the village office, form filling, and physical submission of supporting documents. To overcome this challenge, the proposal of implementing a dedicated information system tailored to streamline the certificate issuance process has emerged. This study proposes a Certificate Service Information System to elevate operational efficiency at the Klamono District Office. The Extreme Programming system development method is utilized, along with testing through Blackbox Testing and Usability Testing. This research indicates that the developed application can improve the effectiveness and efficiency of services in the certificate issuance process. The Blackbox testing results show a system success rate of 100%, while the usability testing report records a user satisfaction level of 93.1%.